2021
DOI: 10.1002/bit.27740
|View full text |Cite
|
Sign up to set email alerts
|

Partitioning metabolism between growth and product synthesis for coordinated production of wax esters in Acinetobacter baylyi ADP1

Abstract: Microbial storage compounds, such as wax esters (WE), are potential high-value lipids for the production of specialty chemicals and medicines. Their synthesis, however, is strictly regulated and competes with cell growth, which leads to trade-offs between biomass and product formation. Here, we use metabolic engineering and synergistic substrate cofeeding to partition the metabolism of Acinetobacter baylyi ADP1 into two distinct modules, each dedicated to cell growth and WE biosynthesis, respectively. We first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…Although wild-type ADP1 naturally produces wax esters as storage compounds, the production metrics are low. Previously, co-feeding of a glycolytic carbon source, gluconate, and acetate was performed with ADP1 Δ aceA overexpressing acr1 (Figure 5A); the strategy enabled partition of carbon source metabolism such that the glycolytic substrate was used for cell growth while acetate could be directed for WE synthesis, allowing enhanced WE accumulation (Santala et al ., 2021). It has also been shown that aceA deletion and acr1 overexpression could lead to improved WE production with high glucose supplementation in the media (Luo et al ., 2020).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although wild-type ADP1 naturally produces wax esters as storage compounds, the production metrics are low. Previously, co-feeding of a glycolytic carbon source, gluconate, and acetate was performed with ADP1 Δ aceA overexpressing acr1 (Figure 5A); the strategy enabled partition of carbon source metabolism such that the glycolytic substrate was used for cell growth while acetate could be directed for WE synthesis, allowing enhanced WE accumulation (Santala et al ., 2021). It has also been shown that aceA deletion and acr1 overexpression could lead to improved WE production with high glucose supplementation in the media (Luo et al ., 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Although glucose was supplemented again at 21 h, it was not consumed by the cells. It is thus important to employ a constant feeding strategy to avoid nutrient depletion, as has been done previously (Santala et al ., 2021). We then cultivated the cells with high glucose concentration; although the WE content of the elongated cells was increased to ∼10% (W/W), it was evident that WE accumulation in the enlarged cells could still be increased.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously engineered the WE production pathway by increasing the availability of the precursor acetyl‐CoA and overexpression of the WE synthesis gene (Lehtinen et al, 2018 ; Luo et al, 2020 ; Santala et al, 2018 ). WE accumulation was also facilitated by employing a strategy that partitioned the carbon sources between growth and WE synthesis (Santala et al, 2021 ). However, cell morphology engineering has not been carried out for WE production.…”
Section: Introductionmentioning
confidence: 99%
“…ADP1 is an ideal model organism for biotechnology and synthetic biology (13) that has been used to study bacterial metabolism, engineering, and evolution (14)(15)(16)(17). The potential of ADP1 as a production host for the synthesis of both native (18)(19)(20)(21)(22) and non-native products (20,23,24) has also been demonstrated. In our previous study, we engineered ADP1 for the production of 1alkenes from ferulate (23), which represents one of the major compounds of alkaline-pretreated lignin (25)(26)(27).…”
Section: Introductionmentioning
confidence: 99%